Dye-Surfactant Interaction: Role of Solvent - Ahmad Khan*, Ziya; S. Al-Bogami, Abdullah (Asian Journal of Chemistry, 2013)
Surfactant-dye associations are important not only in dyeing process but also in dye separation processes such as cloud point extraction or micellar enhanced ultrafiltration. Many techniques were used for qualitative and quantitative description of dye-surfactant interactions, i.e., potentiometry, conductometry, or ion selective electrodes and spectrophotometry. In the presence of surfactant new bands in the electronic absorption spectra of many dyes can appear and the stronger the mutual interaction between dye and surfactant the greater change is observed. The changes of visible absorption spectra of dye in the presence of surfactant at different concentrations result from equilibrium between surfactant monomers, micelles, dye aggregates, dye-surfactant premicellar complex and dye particles incorporated into the micelles. The solvents also plays an important role, as its polarity affects the interaction between the surfactants and dyes. Therefore, the understanding of those interactions enables the prediction of characteristic behaviour of the dye-surfactant mixture in the aqueous and mixed solvent systems. In this paper, we have studied the effect of solvents (especially low per cent) on the interaction of methyl orange with cationic surfactant in presence of various solvents, such as, ethylene glycol, dimethylformamide, dioxane, formamide and acetonitrile.